The Effect of Human Capital, Work Discipline, and Organizational Environment on Employee Performance in Correctional Institutions - Lusiana, Patarida Lonita; Rahmayanti, Rima (Journal of Social Studies Arts and Humanities (JSSAH), 2025)
This study aims to analyze the impact of competence, work discipline, and work environment on employee performance at the Special Guidance Institution for Class II Children (LPKA) Bandung. The research was motivated by a decline in employee performance indicators between 2021 and 2023, reflecting inefficiencies in human resource management. Grounded in the Human Capital Theory, this study examines how competence alignment, employee discipline, and workplace conditions contribute to organizational effectiveness. A quantitative descriptive method was applied using a saturated sampling technique involving all 66 employees of LPKA Bandung. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS version 25. The results show that competence, work discipline, and work environment each have a positive and significant effect on employee performance, both partially and simultaneously. Competence—measured by knowledge, skills, and attitudes—was found to be the most influential factor in enhancing work outcomes, followed by discipline and environmental support. A conducive physical and non-physical work environment also contributes to increased efficiency and motivation. The findings highlight that improving employee competence through targeted training, enforcing discipline policies, and optimizing workplace facilities can substantially enhance performance in public correctional institutions. This study provides practical implications for improving human resource management in government agencies to achieve better service outcomes and institutional accountability.